The last Tosa : Iwasa Katsumochi Matabei, bridge to Ukiyo-e - Kita, Sandy, 1950- (University of Hawaiì Press, 1999)
Iwasa Katsumochi Matabei (1578-1650) is one of the most controversial figures in Japanese art history. For more than half a century, historians have argued over Matabei's role in Japanese art: Was he, as he asserted, "The Last Tosa" (the school of painters who specialized in Yamato-e, a kind of classical courtly painting) or, as others characterized him, "The Founder of Ukiyo-e," the style of painting associated with the urban commoner class. In this highly original and convincing study, Matabei emerges as both - an artist in whose work can be seen elements of both Yamato-e and Ukiyo-e. Extending its analysis beyond the individual artist, The Last Tosa examines the trends and artistic developments of a transitional period and makes heretofore unexamined connections between the world of the aristocrat and the merchant as well as the two artistic schools that reflected their tastes
Keywords: Iwasa, Matabē, -- 1578-1650.; Iwasa, Matabē, -- 1578-1650; Painters -- Japan -- Biography.; Ukiyoe.; Peintres -- Japon -- Biographies.; Ukiyo-e.; BIOGRAPHY & AUTOBIOGRAPHY -- Artists, Architects, Photographers.; ART -- History -- General.; ART -- Asian.; Painters; Ukiyoe; Japan; Humaniora -- Kunst.; Biographies